Corpi dissonanti: note su gender variance e sessualità. Il caso dei femminielli napoletani - Marzia Mauriello (Archivio Antropologico Mediterraneo)
The Neapolitan femminielli, part of the cultural tradition of Naples and its surrounding area, can be considered, following the current terminology, subjects who embody a gender variant. In relation to this “experience of the self”, the author, who has spent almost a decade engaged in field research, here investigates how and when the idea of sexual and gender deviance was constructed and consolidated in so-called Western contexts. Through anthropological analysis of “dissonant bodies”, a metaphor to indicate the different modality, for some subjectivities, of experiencing the self with respect to a constituted order, the analysis shows the cultural, processual and historical nature of the principles of “justice” and “order”, relative to the body and its acts. In reference to the normalization processes within the LGBTQI community – which also come about, for some transgender subjects, through a body that can today change, modify and transform itself seamlessly – and which lead to a re-signification of identity through the body and having a different experience of it, the present study shows how the femminielli embody a different gaze on the experience of the self, and today form a case of cultural resistance.